The Ethical Dilemma of Profit: Evaluating the Triple Bottom Line and the Role of Moral Conscience in Business Decisions - Alowais, Abdelaziz Abdalla (Journal of Ecohumanism, 2024)
A triple bottom line framework (TBL) was gathered to align corporate profit through social and environmental responsibilities that have emerged and gathered widespread adoption and significant criticism. By being praised for a holistic approach to sustainability, considering people, planet, and profit, this is simultaneously criticized for being focused on a financial outcome that often relegates social, environmental, and other concerns to secondary status. The given paper argues for integration into a robust ethical framework, and the most prominent are stakeholder theory and deontological ethics. This demonstrated a utilitarianism that addresses shortcomings. This reforms TBL to more balanced and impactful tools. This was applied to a comparative analysis of businesses that adhere to the traditional TBL practice and incorporate an ethics framework in their model. This study highlighted a potential for improving long-term societal, economic, and environmental impact. The results emphasized an ethical consideration that would be considered an integral external imposition for corporate decision-making. The study ultimately calls for its regulation and policy-level reforms to incentivize companies to adopt ethical concerns through goals for achieving genuine and measurable progress toward sustainability.